Comparative analysis of conventional and organic farming systems: Diversity and abundance of farmland birds - Neumann, Helge; Loges, Ralf; Taube, Friedhelm (2008)
A comparative study on the abundance of breeding birds and wintering birds was carried out over the period 2005-2007 in conventionally and organically managed arable fields in Northern Germany. Birds were surveyed on 40 (breeding season) and 35 (non-breeding season) pairs of fields (conventional/organic), which were selected with regard to similar field sizes, comparable boundary structures (hedges, shrubs) and representative crop rotations. Averaged over three years of investigation, skylarks (Alauda arvensis) and, less distinct, pheasants (Phasianus colchicus) occurred more often on organic fields. In contrast, yellow wagtails (Motacilla flava) showed higher abundances on conventional fields in one year. The diversity of farmland bird species was not affected by farming system (conventional/organic) neither during the breeding season nor during the non-breeding period. Over the winter, carnivore bird species occurred more often in organically managed fields while the total abundance of herbivore species was not affected by farming systems.